Microvascular decompression for neurovascular compression syndromes secondary to vertebrobasilar dolichoectasia: a single-center retrospective analysis - Segura-Lozano, Mauro Alberto; Del Real-Gallegos, Mario Alexis; Mendoza-Lemus, Pedro; Tenorio-González, Bernardo; Torres-Torres, Yael Rodrigo; González-Silva, Alejandro; Carranza-Rentería, Octavio; Parra-Galván, Angel Gabriel; Munguía-Rodríguez, Aarón Giovanni (Frontiers in Surgery, 2025)
BackgroundVertebrobasilar dolichoectasia (VBD) is a rare cause of neurovascular compression syndromes (NVCS), including trigeminal neuralgia (TN), hemifacial spasm (HFS), and glossopharyngeal neuralgia (GPN). Microvascular decompression (MVD) is the primary surgical treatment; however, VBD-related cases are technically challenging and carry a higher risk of complications.ObjectiveTo analyze the clinical characteristics, surgical findings, outcomes, and complications of patients with NVCS secondary to VBD treated with MVD.MethodsA retrospective single-center study was conducted on 68 patients who underwent MVD for VBD-associated NVCS between January 2014 and December 2024. Clinical, imaging, intraoperative, and postoperative data were collected and analyzed. Interposition and transposition techniques were employed according to intraoperative findings.ResultsAmong the 68 patients, TN was present in 49 cases (72.1%), HFS in 7 (10.3%), GPN in 4 (5.9%), and combined neuropathies in 8 (11.8%). Complete symptom relief was achieved in 92.5% of TN/GPN cases and 55.6% of HFS. During follow-up (mean = 27.3 months), TN recurred in 5.3% and HFS in 11.1%. Transient complications occurred in 67.6%, of patients, while persistent deficits were reported in 36.8%. Comparative analysis showed that patients with VBD were older (p < 0.001), predominantly male (p < 0.001), and had a higher prevalence of hypertension (p < 0.001) or diabetes (p = 0.014) compared to those with classical NVCS.ConclusionsMVD remains a safe and effective treatment for NVCS caused by VBD. However, the technical complexity of these cases demands meticulous surgical planning and long-term follow-up. Both interposition and transposition techniques yielded favorable outcomes.